2014
DOI: 10.1002/ange.201402789
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem In Situ Peptide Cyclization through Trifluoroacetic Acid Cleavage

Abstract: We present a new approach for peptide cyclization during solid phase synthesis under highly acidic conditions. Our approach involves simultaneous in situ deprotection, cyclization and trifluoroacetic acid (TFA) cleavage of the peptide, which is achieved by forming an amide bond between a lysine side chain and a succinic acid linker at the peptide N‐terminus. The reaction proceeds via a highly active succinimide intermediate, which was isolated and characterized. The structure of a model cyclic peptide was solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This method allows obtaining the macrocyclic product 81 by the formation of an amide bond between a lysine side chain and a succinic acid linker at the peptide N-terminus in 65% yield. 153 On the other hand, different examples for the syntheses of cyclic peptides where the open-chain precursor is previously released from the resin to perform the macrocyclization in solution can also be found in the literature. 154 In nature, the biosynthetic macrocyclization reaction for the formation of macrocyclic peptides is catalyzed by a thioesterase domain at the C-terminal end of the assembly line.…”
Section: Experimental Aspects In the Synthesis Of Macrocyclesmentioning
confidence: 99%
“…This method allows obtaining the macrocyclic product 81 by the formation of an amide bond between a lysine side chain and a succinic acid linker at the peptide N-terminus in 65% yield. 153 On the other hand, different examples for the syntheses of cyclic peptides where the open-chain precursor is previously released from the resin to perform the macrocyclization in solution can also be found in the literature. 154 In nature, the biosynthetic macrocyclization reaction for the formation of macrocyclic peptides is catalyzed by a thioesterase domain at the C-terminal end of the assembly line.…”
Section: Experimental Aspects In the Synthesis Of Macrocyclesmentioning
confidence: 99%
“…Ring opening by piperidine gives a mixture of d / l ‐ α ‐piperidides and d / l ‐ β ‐piperidides. Ring opening by amino groups leads to the formation of dipeptides or cyclic peptides . In most cases, α ‐piperidides and β ‐piperidides are easily separated from the target peptide by RP‐HPLC; however, resolution of the epimerised α ‐aspartyl peptide is very difficult or impossible .…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53] Recently we have developed an ew peptide cyclization method, in which cyclization between al ysine residue and an N-terminals uccinimide moiety occurs in situ duringt he TFA-mediated peptided eprotection/cleavage step. [54] This indicated that the succinimide moiety is susceptible to nucleophilic attack by amine and might be used for covalenti nhibition as ap recursor for nucleophilic ring opening by nucleophilica mines of the target protein. When the lysine was protected with an acetyl group in the succinyl-LEDGF/p75 peptide, the reaction resulted in the formation of the linear peptide 1 modified with succinimide at its Nterminus instead of ac yclic peptide (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%